Bridgman's complete guide to drawing from life - Bridgman, George Brant, 1864-1943. (New York, N.Y. : Sterling Pub. Co., 2009)
Provides instructions on drawing the human figure.
Originally published: Sterling Pub., 1952.
"Over 1,000 drawings : 22 expert lessons on mastering the figure from every angle"--Cover.
"The classic work on drawing human anatomy"--Cover.
Includes index.
Keywords: Drawing -- Technique; Human figure in art; Anatomy, Artistic